The welcoming attitude of dermatologists towards complementary and alternative medicine despite their lack of knowledge and training - Khalid M. AlGhamdi; Huma Khurrum; Yousif Asiri (Elsevier, 2017)
Background/aim: Although complementary and alternative medicine (CAM) use is highly prevalent, there is very limited information on dermatologists' attitudes and knowledge about CAM. In this survey, we aimed to study the knowledge and attitude of dermatologists in Saudi Arabia towards CAM. Furthermore, we assessed dermatologists' intention to receive CAM education and training. Methods and design: We collected data through an online cross-sectional survey sent to email addresses of dermatologists in Saudi Arabia. Questions included socio-demographic data, knowledge and attitudes towards CAM practice. Results: A total of 93 questionnaires were returned from dermatologists in various regions of Saudi Arabia. The mean age was 41.7 ± 10.3 (range, 25-63) years. A total of 67% of dermatologists had welcoming attitudes towards CAM. We did not find any significant relationship between age, gender, experience or any other factor and positive attitudes towards CAM. More than 70% of participants reported an interest in learning about CAM. However, only 9 (9.7%) dermatologists had attended CAM courses. Sixty-one participants (65.6%) were eager to receive CAM-specific education, and 66% of dermatologists acknowledged having previously discussed CAM with their patients. The most important reason that dermatologists did not discuss CAM with their patients was a lack of studies supporting CAM (66.7%) and the belief that doctors' knowledge on CAM is insufficient (58.1%). Conclusion: A greater number of dermatologists have an affirmative attitude towards CAM. The willingness to improve knowledge and training indicates that the CAM field could potentially grow in dermatology.